Re-thinking HIV-Related Stigma in Health Care Settings: A Qualitative Study - Gagnon, Marilou (Journal of the Association of Nurses in AIDS Care, 2015)
People living with HIV (PLWH) continue to endure stigma and discrimination in the context of health care. This paper presents the findings of a qualitative study designed to (a) describe stigmatizing and discriminatory practices in health care settings, and (b) explore both symbolic and structural stigma from the perspectives of PLWH. For the purpose of this qualitative study, 21 semi-structured in-depth interviews were conducted in the province of Quebec, Canada. The data were analyzed following the principles of thematic analysis. During analysis, three themes were identified, and relations between these themes were delineated to reflect the experiences of participants. The findings suggest that HIV-related stigma in health care settings is episodic in nature. The findings also suggest that HIV-related stigma is experienced through interactions with health care providers (symbolic stigma) and, finally, that it is applied systematically to manage risk in the context of health care (structural stigma).
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; inégalités; justice sociale; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; travail social; trs1205

Psychiatrie, genre et sexualités dans la seconde moitié du XXe siècle - Arena, Francesca; Chiletti, Silvia; Coffin, Jean-Christophe (Comment s'en sortir?, 2015)
Les diagnostics cliniques et les différentes nosographies psychiatriques qui ont été établies dans la deuxième moitié du XXe siècle, notamment dans les différentes éditions du manuel américain de diagnostic et statistique des troubles mentaux (DSM), montrent qu'un nombre très significatif de troubles sont envisagés comme étant genrés. Plusieurs controverses ont marqué l'histoire de ces diagnostics depuis les années 1950 : d'abord celui des sexualités et de leurs frontières floues, ensuite la notion controversée d'identité de genre, enfin la problématique des troubles périnataux. Si le principe de différentiation constitue un élément incontournable de la pensée psychiatrique, le façonnage et l'usage du concept de « genre » révèlent des tensions entre la psychiatrie et la société (notamment les mouvements gay, féministes et trans) mais aussi au sein de la psychiatrie elle-même. Il apparaît évidant que, dans les classifications psychiatriques, les normes sociales de genre sont intégrées de manière passive et acritique, au point que l'usage du concept de genre peut amener à l'inverse à renforcer la naturalisation des comportements alors même que, dans les sciences sociales, il est utilisée pour interroger et déconstruire la prétendue naturalité de la différence des sexes.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; sofia; systèmes d'oppressions; thématiques; violences; états-unis

Working women in transition to motherhood in Italy - Bertolini, Sonia; Musumeci, Rosy; Naldini, Manuela; Torrioni, Paola Maria (Journal of Romance Studies, 2015)
This article deals with the changing relationship between work and motherhood during the first pregnancy among a group of twenty-one highly educated women living in Turin (Northern Italy), who were interviewed during the months before childbirth with their male partners, in 2010-2012. It aims to illustrate the tensions between the dominant ideas and ideals of motherhood (the 'intensive mothering' model) and the pressing demands of the changing labour market. The data shows that ideas, plans and decisions concerning childcare arrangements are highly gendered, being influenced by the expectations of partners, employers and colleagues and by a work culture which is not family friendly. Within this Italian social and political context, a mother-to-be faces a dilemma which is perceived as a private issue that concerns only herself. The new transition to parenthood forces women to redefine their identity and career in a highly gendered manner. © Institute of Modern Languages Research 2015.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; charge mentale; conciliation famille-travail; europe; famille; italie; maternité; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques; travail

Le care : éthique féministe actuelle - Bourgault, Sophie; Perreault, Julie (Les éditions du remue-ménage, 2015)
Cet ouvrage présente une réflexion pluridisciplinaire sur l'éthique féministe du care. Élaborée par Carol Gilligan dans In a Different Voice en 1982, cette «éthique de la sollicitude» a été très prisée dans les années 1980. Plus récemment, nous assistons à l'émergence d'une enthousiaste seconde génération de théoricien.ne.s du care qui y voient un terreau fertile pour réfléchir aux oppressions liées à la division genrée du travail.Comment ce renouveau se traduit-il? Quels sont les enjeux éthiques, politiques et épistémologiques que permet de mettre en lumière cette approche? Le care équivaut-il essentiellement au travail de soin effectué en majorité par les femmes, ou comprend-il l'ensemble des services domestiques, affectifs et sexuels fournis dans un rapport d'interdépendance?L'originalité de ce premier ouvrage faisant le point sur la question au Québec tient entre autres à son souci constant de débarrasser le care du sentimentalisme qu'on lui a souvent reproché, et surtout, de le réinvestir de tout son potentiel critique et féministe.Avec des textes de Bettina Bergo, Agnès Berthelot-Raffard, Sophie Bourgault, Sophie Cloutier, Marjolaine Deschênes, Stéphanie Gaudet, Naïma Hamrouni, Mariko Konishi, Monique Lanoix, Patricia Paperman et Julie Perreault.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; discours dominant; division sexuelle du travail; inégalités; patriarcat; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; santé mentale; systèmes d'oppressions; thématiques; travail

Anna, salle d'attente - Cornu, Emmanuelle (Druide, 2015)
Anna a vingt-sept ans et n’a pas rencontré le grand amour. Elle saute quelques étapes dans son existence de jeune lesbienne et décide d’entrer dans la course à la maternité. Michaëlle, une globetrotteuse volage, vient bouleverser ses plans. C’est le coup de foudre. Anna tombe de haut et se voit confrontée à une décision douloureuse : nourrir son affection pour Michaëlle ou poursuivre son rêve parental. Dans le doute, Anna préfère une troisième option : elle abandonne les inséminations, opte pour l’adoption, puis s’acharne à transformer son amante en épouse fidèle. Les rêves d’Anna volent en éclats. De crise en crise, Anna tente de sortir de son marasme, mais s’enfonce dans la dépression. Anna troque une salle d’attente pour une autre.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; hétérosexisme; maternité; périodes historiques; québec; régions géographiques; santé; systèmes d'oppressions; thématiques

Sorcières, sages-femmes et infirmières : une histoire des femmes soignantes - Ehrenreich, Barbara; English, Deirdre (Cambourakis, 2015)
Engagées dans le Mouvement pour la santé des femmes dans les années 1970, Barbara Ehrenreich et Deirdre English enquêtent sur les racines historiques de la professionnalisation du corps médical. Portant un regard féministe sur les chasses aux sorcières en Europe et la suppression de la profession de sage-femme aux Etats-Unis, elles s'interrogent : et si, derrière ces événements, se cachait une véritable monopolisation politique et économique de la médecine par les hommes de la classe dominante, reléguant peu à peu les femmes à la fonction subalterne d'infirmière docile et maternelle ? Depuis sa parution aux Etats-Unis en 1973, cet essai concis et incisif a ouvert la voie à de nombreux travaux de recherche et prises de conscience. Cette traduction s'ouvre sur une préface inédite des deux auteures.
Première publication: 1973
Keywords: approches et analyses; com5170; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem7000; histoire; lit2815; lit3220; lit3495; occident; premier cycle; santé; santé reproductive; sciences humaines; sorcière; systèmes d'oppressions; thématiques; violences; violences gynécologiques et obstétricales

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Medical industrial complex visual - Mingus, Mia (Leaving Evidence, 2015)
The following is a visual* of the Medical Industrial Complex (MIC) and is offered as a tool for our work for collective liberation.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capacitisme; cours; discours dominant; eugénisme; fem3300; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; états-unis

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle